The Effect of Metal-Semiconductor Contact on the Transient Photovoltaic Characteristic of HgCdTe PV Detector - Haoyang Cui; Yongpeng Xu; Junjie Yang; Naiyun Tang; Zhong Tang (The Scientific World Journal)
The transient photovoltaic (PV) characteristic of HgCdTe PV array is studied using an ultrafast laser. The photoresponse shows an apparent negative valley first, then it evolves into a positive peak. By employing a combined theoretical model of pn junction and Schottky potential, this photo-response polarity changing curves can be interpreted well. An obvious decreasing of ratio of negative valley to positive peak can be realized by limiting the illumination area of the array electrode. This shows that the photoelectric effect of Schottky barrier at metal-semiconductor (M/S) interface is suppressed, which will verify the correctness of the model. The characteristic parameters of transient photo-response induced from p-n junction and Schottky potential are extracted by fitting the response curve utilizing this model. It shows that the negative PV response induced by the Schottky barrier decreases the positive photovoltage generated by the pn junction.